Genetic diversity of Leptospira in northwestern Colombia: first report of Leptospira santarosai as a recognised leptospirosis agent (2016)
ABSTRACT: The region of Antioquia in northeastern Colombia has the highest number of reported leptospirosis cases in the country. It also shows high seroprevalence indexes in the general population and socio-environmental conditions favourable for the transmission of the disease between humans and animals. In this study, 25 Leptospira isolates from Colombia’s Antioquia department were identified to the species level as L. santarosai (12), L. interrogans (9) and L. meyeri (4) using phylogenetic analysis of the Amidohydrolase gene. Typing at the serovar level was performed using multilocus sequence typing (MLST) and monoclonal antibodies. The serovars Canalzonae, Babudieri, Alice, Beye, and Copenhageni have been identified as causing human or animal infections in Antioquia, Colombia. The four environmental isolates were not identified to the serovar level. L. santarosai serovar Canalzonae and Alice were identified as new etiologic agents of human leptospirosis in Antioquia, Colombia. This paper reports species and serovars that were previously unknown in the region.